FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Andreas Bambang Daryatno (Universitas Multimedia Nusantara, 2022)
Abstract - The purpose of this study is to obtain empirical evidence of the effect of loan to deposit ratio, firm size and GDP on the company's financial performance which is represented by return on equity in banking companies listed on the Indonesia Stock Exchange in 2018-2020. This study uses purposive sampling as a sampling technique and uses banking companies as research samples. The data used in this study comes from the financial statements of banking companies listed on the Indonesia Stock Exchange. Data processing in this study using the Smart Pls3 program. The results obtained that the loan to deposit ratio has a positive but not significant effect on financial performance, while firm size and gross domestic product have a positive and significant effect on financial performance. High credit delivery rates must be accompanied by good credit quality so that banking losses are low, this happened in Indonesia where gross NPL during 2020 during the pandemic only reached 3.06 percent, up from 2019 gross NPL which reached 2.5 percent and The 2018 gross NPL which reached 2.37 means that OJK has succeeded in restraining the increase in NPL through POJK 11/2020 regulation on credit restructuring. The confidence of the Indonesian people in the big show and the maintained GDP of Indonesia keeps investors optimistic and keeps investing, this will certainly accelerate the economic recovery and increase income for banking in Indonesia. It boils down to an increase in income or credit sales, which in turn will improve the financial performance of banks. Keywords: Financial Performance; Loan to Deposit Ratio; Firm Size; GDP